2015
DOI: 10.3762/bjnano.6.86
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of hydrogen titanate nanoribbons to TiO2 nanoribbons and the influence of the transformation strategies on the photocatalytic performance

Abstract: SummaryThe influence of the reaction conditions during the transformation of hydrogen titanate nanoribbons to TiO2 nanoribbons on the phase composition, the morphology, the appearance of the nanoribbon surfaces and their optical properties was investigated. The transformations were performed (i) through a heat treatment in oxidative and reductive atmospheres in the temperature range of 400–650 °C, (ii) through a hydrothermal treatment in neutral and basic environments at 160 °C, and (iii) through a microwave-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 51 publications
(76 reference statements)
3
37
0
Order By: Relevance
“…8a, un-treated TiAR showed a strong signal at g ¼ 2.01 and a broad peak at g ¼ 1.981, which were ascribed to V O and unsaturated Ti 3+ , respectively. [47][48][49] For TiAR(H 2 ), an extra new peak for Ti 3+ (g ¼ 1.999) appeared, and the peak intensity for V O increased slightly. This result indicated that H 2 treatment led to the formation of more Ti 3+ /V O on TiAR(H 2 ), which was consistent with literature reports.…”
Section: Chemical State and Surface Chemistrymentioning
confidence: 97%
See 1 more Smart Citation
“…8a, un-treated TiAR showed a strong signal at g ¼ 2.01 and a broad peak at g ¼ 1.981, which were ascribed to V O and unsaturated Ti 3+ , respectively. [47][48][49] For TiAR(H 2 ), an extra new peak for Ti 3+ (g ¼ 1.999) appeared, and the peak intensity for V O increased slightly. This result indicated that H 2 treatment led to the formation of more Ti 3+ /V O on TiAR(H 2 ), which was consistent with literature reports.…”
Section: Chemical State and Surface Chemistrymentioning
confidence: 97%
“…First, TiAB had multiple peaks at g ¼ 1.971-1.991, g ¼ 2.007, and g ¼ 2.023, which were attributed to Ti 3+ sites, V O and super-oxygen ions (O 2 À ), respectively. 47,[49][50][51] The formation of O 2 À species was possibly due to the attachment of electrons stored in V O to adsorbed O 2 molecules. Second but more importantly, the intensity of Ti 3+ on TiAB was much stronger than that on TiAR, indicating TiAR had a higher content of Ti 3+ .…”
Section: Chemical State and Surface Chemistrymentioning
confidence: 99%
“…It is because of the fact, that surface wettability and surface energy, which influence mentioned activity, are closely related to surface morphology. Among different titania architectures nanoparticles [38,39], nanotubes [40,41], nanofibers [42], nanowires [43], nanorods [43,44], nanobelts [43,45], nanoribbons [46], are the most important and often studied. The diversity of TiO 2 nanoarchitecture results from a wide range of applied experimental methods for the synthesis of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…After polymer decomposition via thermal treatment, mesoporous materials with high surface area and pore volume are obtained [ 13 15 ]. The increase in surface area depends on the type of polymer added, the type of oxides and on the stage of synthesis during which the polymer is added [ 16 18 ]. The specific surface area can also be increased by decreasing the particle size of TiO 2 ; however, it has been shown that the photocatalytic activity does not monotonically increase with decreasing particle size, but rather there exists an optimal particle size for pure nanocrystalline TiO 2 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%